Abiraterone acetate treatment lowers 11-oxygenated androgens. Issue 4 (April 2020) - Wright, Connor; O'Day, Patrick; Alyamani, Mohammed; Sharifi, Nima; Auchus, Richard J
Abstract : Context: The human adrenal is the dominant source of androgens in castration-resistant prostate cancer (CRPC) and classic 21-hydroxylase deficiency (21OHD). Abiraterone, derived from the prodrug abiraterone acetate (AA), inhibits the activity of cytochrome P450 17-hydroxylase/17, 20-lyase (CYP17A1), the enzyme required for all androgen biosynthesis. AA treatment effectively lowers testosterone and androstenedione in 21OHD and CRPC patients. The 11-oxygenated androgens are major adrenal-derived androgens, yet little is known regarding the effects of AA administration on 11-oxygenated androgens. Objective: To test the hypothesis that AA therapy decreases 11-oxygenated androgens. Design: Samples were obtained from 21OHD or CRPC participants in AA or AA plus prednisone (AAP)-treatment studies, respectively. Methods: We employed liquid chromatography-tandem mass spectrometry (LC-MS/MS) to measure the 11-oxygenated androgens, 11β-hydroxyandrostenedione, 11-ketoandrostenedione, 11β-hydroxytestosterone, and 11-ketotestosterone, in plasma or serum samples from six 21OHD and six CRPC patients before and after treatment with AA or AAP, respectively. Results: In CRPC patients, administration of AAP (1000 mg/day AA with prednisone and medical castration) lowered all four 11-oxygenated androgens to below the lower limits of quantitation (<0.1–0.3 nmol/L), equivalent to 64–94% reductions from baseline. In 21OHD patients, administration of AA (100–250 mg/day for 6 days) reduced all 11-oxygenated androgens by on average 56–77% from baseline. Conclusions: We conclude that AA and AAP therapies markedly reduce the production of the adrenal-derived 11-oxygenated androgens, both in patients with high (21OHD) or normal (CRPC) 11-oxygenated androgens at baseline, respectively. Reduction of 11-oxygenated androgens is an important aspect of AA and AAP pharmacology.